Shared Capitalism at Work 2010
DOI: 10.7208/chicago/9780226056968.003.0009
|View full text |Cite
|
Sign up to set email alerts
|

Do Workers Gain by Sharing? Employee Outcomes under Employee Ownership, Profit Sharing, and Broad-Based Stock Options

Abstract: This paper examines how shared capitalism compensation systems -those that link employee pay to company performance -affect diverse employee outcomes. It uses two data sets: the national GSS survey that provides a broad representative view of the extent of the programs; and the NBER Shared Capitalism Project surveys of workers in 14 companies that use shared capitalism programs extensively. We find that greater involvement in the programs is generally linked to greater participation in decisions, higher qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 25 publications
2
86
1
1
Order By: Relevance
“…A recent analysis of shirking, using two major US databases, found that shirking is not confined to workplaces that have adopted "shared capitalism" (profit sharing, employee stock plans, and the like) but is also common in other workplaces [6]. The study posits that, contrary to the free-rider argument, workers in such arrangements may engage in "mutual monitoring" and may intervene with workers who are perceived to be putting forth insufficient effort.…”
Section: The Free-rider Problemmentioning
confidence: 47%
See 2 more Smart Citations
“…A recent analysis of shirking, using two major US databases, found that shirking is not confined to workplaces that have adopted "shared capitalism" (profit sharing, employee stock plans, and the like) but is also common in other workplaces [6]. The study posits that, contrary to the free-rider argument, workers in such arrangements may engage in "mutual monitoring" and may intervene with workers who are perceived to be putting forth insufficient effort.…”
Section: The Free-rider Problemmentioning
confidence: 47%
“…The empirical results indicate that workers are most likely to intervene with shirkers in companies that have some form of employee profit sharing and where employees participate in decisions or work in teams [6].…”
Section: The Free-rider Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…They interact a measure of pay with an index of shared capitalism. Kruse et al (2008) find that "greater involvement in the programs (shared compensation schemes) is generally linked to greater participation in decisions, higher quality supervision and treatment of employees, more training, higher pay and benefits, greater job security, and higher job satisfaction".…”
Section: Literaturementioning
confidence: 99%
“…The most recent evidence comes from an NBER project: see, for example Freeman (2008), Blasi et al (2008) and Kruse et al (2008). Freeman (2008) concentrates on the idea that worker co-monitoring can get around the free-rider problem.…”
Section: Literaturementioning
confidence: 99%